Studi Orientalis Atas Hadis Nabi (Konsep Pemikiran Ignaz Goldziher Terhadap Hadis Nabi) - Lutfiah Adhwa; Al-Ikhwanul Nirwan; Ira Mufida; Novia Rahma Lihawa; Nanda Nanda (Publikasi Indonesia, 2025)
This study aims to analyze the Orientalist perspective of Ignaz Goldziher on the Hadith of Prophet Muhammad (PBUH), particularly his distinction between hadith and sunnah, as well as his criticism of the authenticity of hadith texts. Goldziher was a prominent 19th-century Orientalist whose work, Muhammedanische Studien, became a foundational reference in modern Western Hadith studies. This research employs a qualitative method using a literature review approach, gathering data from primary and secondary sources related to Goldziher's thoughts and the critical responses to them. The findings reveal that Goldziher viewed hadith not as original Islamic documents from the early period, but as socio-political constructions developed during the first and second centuries of Hijrah. He distinguished sunnah as a social tradition and hadith as a doctrinal product. However, his views were met with strong rebuttals from Muslim scholars such as M.M. Azami, who defended the scientific and historical authenticity of hadith.This study highlights a sharp methodological divide between Western Orientalists and Muslim scholars in understanding hadith, emphasizing the importance of critical and historical approaches in contemporary Islamic studies.